ANALISIS BENTUK POLITICAL PARTICIPATORY CULTURE FANBASE ANIES BASWEDAN - Arrafii, Aqil; Syammas, Ilyasa; Rumahorbo, Yuslin Ridho Julio (Jurnal Media dan Komunikasi, 2025)
This study examines the phenomenon of the "Humanies Project" political fandom as a form of participatory culture supporting Anies Baswedan during the 2024 Presidential Election campaign. Using digital ethnography methods, the research explores the elements of affiliation, expression, collaboration, and circulation manifested by this community through the social media platform X (formerly Twitter). Data were collected through digital documentation, such as posts, comments, and content from the Humanies Project account, and analyzed qualitatively. The findings reveal that the Humanies Project significantly contributes to building a collective political identity, particularly among younger generations. Popular cultural elements such as K-Popfication, food trucks, and light sticks were employed to creatively and engagingly convey political messages. Furthermore, the "haveaniesday.com" website emerged as a digital artifact that strengthens political engagement through interactive narratives and designs. These findings highlight the potential of political fandoms to enhance youth political participation through approaches aligned with the digital era. This research aims to serve as a reference for studies on political communication and popular culture and provide insights into community-based campaign strategies that are more inclusive and dynamic.